Mice lacking NMDA receptors in parvalbumin neurons display normal depression-related behavior and response to antidepressant action of NMDAR antagonists. - Laura Pozzi (Public Library of Science (PLoS), 2014)
The underlying circuit imbalance in major depression remains unknown and current therapies remain inadequate for a large group of patients. Discovery of the rapid antidepressant effects of ketamine--an NMDA receptor (NMDAR) antagonist--has linked the glutamatergic system to depression. Interestingly, dysfunction in the inhibitory GABAergic system has also been proposed to underlie depression and deficits linked to GABAergic neurons have been found with human imaging and in post-mortem material from depressed patients. Parvalbumin-expressing (PV) GABAergic interneurons regulate local circuit function through perisomatic inhibition and their activity is NMDAR-dependent, providing a possible link between NMDAR and the inhibitory system in the antidepressant effect of ketamine. We have therefore investigated the role of the NMDAR-dependent activity of PV interneurons for the development of depression-like behavior as well as for the response to rapid antidepressant effects of NMDAR antagonists. We used mutant mice lacking NMDA neurotransmission specifically in PV neurons (PV-Cre+/NR1f/f) and analyzed depression-like behavior and anhedonia. To study the acute and sustained effects of a single NMDAR antagonist administration, we established a behavioral paradigm of repeated exposure to forced swimming test (FST). We did not observe altered behavioral responses in the repeated FST or in a sucrose preference test in mutant mice. In addition, the behavioral response to administration of NMDAR antagonists was not significantly altered in mutant PV-Cre+/NR1f/f mice. Our results show that NMDA-dependent neurotransmission in PV neurons is not necessary to regulate depression-like behaviors, and in addition that NMDARs on PV neurons are not a direct target for the NMDAR-induced antidepressant effects of ketamine and MK801.